Effects of decompressive surgery on prognosis and cognitive deficits in herpes simplex encephalitis - MİDİ, İPEK (IOS PRESS, 2007)
Herpes simplex. encephalitis (HSE) is a serious viral infection with a high rate of mortality. The most commonly seen complications are behavioral changes, seizures and memory deficits. We report the case of a 37-year-old man with HSE in the right temporal lobe and a severe midline shift who was treated with acyclovir. The patient underwent anterior temporal lobe resection. Although HSE can cause permanent cognitive deficits, in this case, early surgical intervention minimized any deficit, as determined by detailed neuropsychological examination. Surgical decompression is indicated as early as possible in severe cases. This case report emphasizes the effect of surgical decompression for HSE on cognitive function, which has rarely been mentioned before.
Keywords: herpes simplex encephalitis; decompressive craniotomy; anterior temporal lobe; cognition